Adults and young people in the mirror between emotional crisis and digital culture. Affective education as a formative bet - Simona Perfetti (University of Bologna, 2023)
Today, the persistence of infantile attitudes into adulthood seems to have become a way of life associated with enjoyment and the renunciation of social obligations. Contemporary society, crossed by the emotional culture of Social Media, favors the example of parents who are friends with their children, of teachers who are enemies of their parents and of young people who are far from authority and traditional morality. Distances between parents and children and between teachers and pupils are eliminated. Today's adolescent is represented with the image of Narcissus because within the affective family he grows up with the idea that success is the goal for achieving happiness and personal satisfaction. What future prospects can you imagine for young people? How to tackle adult frailty? The pedagogical debate could reflect on new educational systems that concern the affective and relational dimension of young people and the orientation skills of adults. By accepting the new needs of young people, adults could carry out that progressive process of affectivity, the acceptance of new educational, affective and relational functions.